Pengaruh Kepercayaan, Nisbah bagi Hasil dan Persepsi Risiko terhadap Keputusan Pemilihan Produk Deposito IB - Almeyda, Devia; Canggih, Clarashinta (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The increasing number of Islamic bank term deposit account indicates attract attention in sharia deposits. An in crease in the number of deposit accounts can be caused by several factors. This study aims to determine the effect of trust, profit sharing ratio and perceived risk on the decision to choose Islamic bank term deposit. The samples used in this study were 108 respondents Islamic bank deposit customers in Sidoarjo and Surabaya that are determined by purposive sampling. The analytical method used is Confirmatory Factor Analysis (CFA). The result of this study indicated that trust has an effect on the decision to choose Islamic bank deposit, while profit sharing ratio and perceived risk have no effect on the decision to choose Islamic bank deposit. With the results of this study, it is hoped that future researchers can do further research related to the decision to choose deposit products at different Islamic Banks in the community and add other variables such as literacy and spirituality levels so that they can correct existing deficiencies.